Correlation of in-vivo imaging with histopathology: A review. Issue 144 (November 2021) - Sen, Anando; Troncoso, Patricia; Venkatesan, Aradhana; Pagel, Mark D.; Nijkamp, Jasper A.; He, Yulun; Lesage, Anne-Cecille; Woodland, McKell; Brock, Kristy K.
Highlights: Discussing the steps of imaging-pathology correlation with emphasis on 62 studies. Challenges and fallacious assumptions prevalent in correlative pathology studies. A statistical analysis of imaging-pathology registration accuracy for 19 studies. Looking ahead to the future of correlative pathology studies. Abstract: Despite tremendous advancements in in vivo imaging modalities, there remains substantial uncertainty with respect to tumor delineation on in these images. Histopathology remains the gold standard for determining the extent of malignancy, with in vivo imaging to histopathologic correlation enabling spatial comparisons. In this review, the steps necessary for successful imaging to histopathologic correlation are described, including in vivo imaging, resection, fixation, specimen sectioning (sectioning technique, securing technique, orientation matching, slice matching), microtome sectioning and staining, correlation (including image registration) and performance evaluation. The techniques used for each of these steps are also discussed. Hundreds of publications from the past 20 years were surveyed, and 62 selected for detailed analysis. For these 62 publications, each stage of the correlative pathology process (and the sub-steps of specimen sectioning) are listed. A statistical analysis was conducted based on 19 studies that reported target registration error as their performance metric. While some methods promise greater accuracy, they may be expensive. Due to the complexity of the processes involved, correlative pathology studies generally include a small number of subjects, which hinders advanced developments in this field.